The book of Greek & Roman folktales, legends, & myths - Hansen, William F., 1941-; Fawkes, Glynnis (Princeton, New Jersey : Princeton University Press, 2017)
The first anthology ever to present the entire range of ancient Greek and Roman stories--from myths and fairy tales to jokes Captured centaurs and satyrs, talking animals, people who suddenly change sex, men who give birth, the temporarily insane and the permanently thick-witted, delicate sensualists, incompetent seers, a woman who remembers too much, a man who cannot laugh--these are just some of the colorful characters who feature in the unforgettable stories that ancient Greeks and Romans told in their daily lives. Together they created an incredibly rich body of popular oral stories that include, but range well beyond, mythology--from heroic legends, fairy tales, and fables to ghost stories, urban legends, and jokes. This unique anthology presents the largest collection of these tales ever assembled. Featuring nearly four hundred stories in authoritative and highly readable translations, this is the first book to offer a representative selection of the entire range of traditional classical storytelling. Set mostly in the world of humans, not gods, these stories focus on figures such as lovers, tricksters, philosophers, merchants, rulers, athletes, artists, and soldiers. The narratives range from the well-known--for example, Cupid and Psyche, Diogenes and his lantern, and the tortoise and the hare--to lesser-known tales that deserve wider attention. Entertaining and fascinating, they offer a unique window into the fantasies, anxieties, humor, and passions of the people who told them. Complete with beautiful illustrations by Glynnis Fawkes, a comprehensive introduction, notes, and more, this one-of-a-kind anthology will delight general readers as well as students of classics, fairy tales, and folklore.
SAGES AND PHILOSOPHERS. Truth and Wisdom -- The Seven Sages and the Prize of Wisdom -- Thales on Life and Death -- A Question of Responsibility -- A Problem of Identity -- Secundus the Silent Philosopher -- Converting to Philosophy -- Plato -- Axiothea -- Epicurus -- Benefits and Perils of Philosophy -- Aristippos on the Philosopher's Advantage -- Aristippos on the Benefits of Philosophy -- Antisthenes on the Benefits of Philosophy -- Diogenes on the Benefits of Philosophy -- Krates on the Benefits of Philosophy -- The Most Useful Man in Ephesos -- Protagoras's Books Burned -- Sinning against Philosophy -- The Philosophic Life -- Thales in the Well -- Thales and the Olive Presses -- Wealth vs Wisdom -- Simonides's View -- Aristippos's View -- The Cynics -- Diogenes on Being Laughed At -- Diogenes and the Lantern -- The Meeting of Diogenes and Alexander -- Alexander's Offer -- Diogenes on Personal Attire -- Diogenes on Temple Theft -- Diogenes on a Public Reading -- Diogenes Visits a Brothel -- Diogenes on the City of Myndos -- Watch Out! -- Krates and Hipparchia -- Monimos on Wealth -- Philosophers Criticize One Another -- Diogenes Criticizes Plato -- Plato Criticizes Diogenes -- Plato Characterizes Diogenes -- Diogenes on Plato's Theory of Ideas -- Diogenes on a Definition of Plato's -- Diogenes on the Impossibility of Motion -- Education and Learning -- A Song before Dying -- The Entrance to Plato's Classroom -- The Delian Problem -- The Worst Punishment -- Discoveries and Inventions -- The Invention of Hunting -- The Invention of Board Games -- The Original Language -- Thales Inscribes a Triangle in a Circle -- Thales Measures the Height of the Pyramids -- Thales Predicts an Eclipse -- The Pythagorean Theorem -- Eureka! -- Happiness and Contentment -- The Origin of Human Miseries -- The Rock of Tantalos -- The Sword of Damocles -- King Midas -- Wealth and Happiness -- Water and a Loaf of Bread -- Gold vs Figs -- Untouched by Grief -- The Happy Mute -- Pyrrhos and Kineas -- Drinking -- The Third Cup of Wine -- On Behaving Like Animals -- The Different Stages of Life -- The Different Kinds of People -- The Different Kinds of Women -- Aesopic Fables -- The Fox and the Crane -- The Dog with a Piece of Meat -- The Raven with a Piece of Meat -- The King of the Apes -- The Ape with Important Ancestors -- The Sour Grapes -- The Ant and the Cicada -- The Lion's Share -- The Race of the Tortoise and the Hare -- The Lion and the Mouse -- The Plump Dog -- The Transformed Weasel -- The Goose That Lays Golden Eggs -- The Tortoise That Wishes to Fly -- The King of the Frogs -- The Astronomer -- The Shepherd Who Cries -Wolf ! -- Here Is Rhodes! -- The Belly and the Feet -- The Oak and the Reed -- Short Fables -- The Mountain in Labor -- The Attentive Donkey -- NUMSKULLS AND SYBARITES. Traditional Numskulls -- Margites -- Meletides -- Koroibos -- Morychos -- Akko -- The Foolish Kymaians -- The Foolish Abderites -- Other Numskulls -- Carrying the Load -- Acquiring Sense -- Seeing the Doctor -- The Trained Donkey -- The Books -- The Slave -- A Call of Nature -- The Twins -- The Funeral -- The Ball in the Well -- The Educated Son -- The Travelers -- The Grateful Father -- A Pair of Twins -- The Fugitives -- The Pillow -- Wits -- Too Healthy -- What Does It Taste Like? -- All in the Family -- The Strongest Thing -- Caesar's Soldiers Sing -- Miscellaneous -- Not at Home -- The Portent -- The Deaf Judge -- The Scythian -- The Cold Reading -- The Covetous Man and the Envious Man -- The Delicate Sybarites -- Uncomfortable Sleep -- The Suitor -- Noise Policy -- The Affliction of Work -- Excursions to the Country -- Chamber Pots -- Piped Wine -- Policy on Parties -- Dancing Horses -- Tall Tales -- Topsy-Turvy Land -- Frozen Speech -- Thin Men -- Appendix Across the Genres: Ancient Terms, Belief, and Relative Numbers -- Notes on the Tales -- Glossary -- Bibliography -- Ancient Sources -- List of International Stories.
Includes bibliographical references and index.
Keywords: Mythology, Greek; Mythology, Roman; Mythology, Greek; Mythology, Roman